The Influence of Self-Efficacy, Work Ethic, and Work Discipline on Employee Performance at the Secretariat of the Regional People's Representative Council (DPRD) of Kerinci Regency - Efrianto, Efrianto; Hamdani, Deky; Hendra, Hendra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the influence of self-efficacy, work ethic, and work discipline on the performance of daily contract employees at the Secretariat of the Regional People's Representative Council (DPRD) of Kerinci Regency. The main issue identified is the mismatch between compensation and workload, which has the potential to reduce employee motivation and productivity. This study uses a quantitative approach with a survey method, involving 20 respondents selected through purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The results show that self-efficacy, work ethic, and work discipline significantly affect employee performance, both simultaneously and partially. Self-efficacy has the most dominant influence compared to the other variables, with a regression coefficient of 0.45. The coefficient of determination (R²) of 0.68 indicates that 68% of the variation in employee performance can be explained by the three independent variables. Based on these findings, it is recommended that the organization improve self-efficacy through training, strengthen a positive work culture, and establish a fairer compensation system.